Neonatal meningitis caused by streptococcus pneumonia in Iran - zahra abbasi shaye; ehsan alaee; Maryam Abbasi shaye; matin bakhtiari (Mashhad University of Medical Sciences, 2015)
Meningitis, pneumonia, and sepsis in newborns and young infants (age < 60 days) are the main causes of childhood mortality in developing countries. Even though streptococcus pneumonia is the most commonly detected microorganism in pediatric bacterial meningitis, it is rare in newborn infants. The following article reports a case of pneumococcal meningitis that was detected early in a newborn infant in 2013. A female baby was born by vaginal delivery with a birth weight of 2900 grams. She was symptomatic (poor feeding) from her first day of life, but she was admitted with a toxic status (dehydrated, lethargic, cyanotic, hypo tone, hypo reflex) to our referral center on her third day life. Her blood culture showed no growth of any organism and her urine culture was also negative, but the Cerebrospinal fluid (CSF) culture showed growth of streptococcus pneumonia. The maternal sepsis workup was normal. Despite all therapeutic management, unfortunately, the patient died on her fourth day after admission.